Neoadjuvant chemotherapy plus radical cystectomy versus radical cystectomy alone in clinical T2 bladder cancer without hydronephrosis. (21st November 2020) - Soria, Francesco; Black, Peter C.; Fairey, Adrian S.; Cookson, Michael S.; Yu, Evan Y.; Kassouf, Wassim; Dall'Era, Marc A.; Sridhar, Srikala S.; McGrath, John S.; Wright, Jonathan L.; Thorpe, Andrew C.; Morgan, Todd M.; et al.
Abstract : Objectives: To assess the efficacy of neoadjuvant chemotherapy (NAC) before radical cystectomy (RC) in a retrospective multicentre cohort of patients with cT2N0M0 bladder cancer (BCa) without preoperative hydronephrosis. Patients and Methods: This was a propensity‐based analysis of 619 patients. Of these, 316 were treated with NAC followed by RC and 303 with upfront RC. After multiple imputations, inverse probability of treatment weighting (IPTW) was used to account for potential selection bias. Multivariable logistic regression analysis was performed to evaluate the impact of NAC on pathological complete response and downstaging at RC, while IPTW‐adjusted Kaplan–Meier curves and Cox regression models were built to evaluate the impact of NAC on overall survival (OS). Results: After IPTW‐adjusted analysis, standardised differences between groups were <15%. A complete response (pT0N0) at final pathology was achieved in 94 (30%) patients receiving NAC and nine (3%) undergoing upfront RC. Downstaging to non‐muscle‐invasive disease (<pT2N0M0) was observed in 174 (55%) patients after NAC and in 72 (24%) without NAC. On multivariable analysis, NAC was found to be an independent predictor of both pathological complete response and downstaging. No significant difference with respect to OS was observed between groups with a median follow‐up of 18 months. Conclusions: In patients with cT2N0 BCa and no preoperative hydronephrosis, NAC increased the rate of pathological complete response and downstaging.